TO THE QUESTION OF CREATION OF AUTOMATED SYSTEM OF OPERATION OF RAILWAY ARTIFICIAL CONSTRUCTIONS - Borshchov, V. I. (Science and Transport Progress, 2004)
The paper considers the issues, related to creation of automated maintenance system of artificial structures on a separately taken railway. A probable structure of the system is described, its operational modes are considered. The aggregative flow-chart of the structures’ maintenance system has been provided.